Investment Decision, Funding Decisions, And Dividend Policies On Firm Value: Empirical Evidence From Emerging Country - Lutfatul Jamiah; Sukrisno Sukrisno (UNIVED Press, 2026)
This study aims to examine the influence of investment decision, funding decision, and dividend policies on the value of non finance companies listed on the Indonesia Stock Exchange for the period 2019 to 2023. The study population included all non finance companies listed on the Indonesia Stock Exchange, and sample selection was carried out using purposive sampling techniques with criteria of consistency of financial reporting, cash dividend distribution, and completeness of data during the observation period. This study uses secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange and analyzed using multiple linear regression using the Ordinary Least Squares method through SPSS software version 26. The results of the study show that. Simultaneously, Debt to Equity Ratio (DER) ,Price Earnings Ratio (PER ) and Price to Book Value (PBV),have a significant effect on the company's value with adequate model explainability. This study provides theoretical implications in the form of strengthening signaling theory and trade-off theory, managerial implications in the form of the importance of stable dividend policy priorities, and regulatory implications in the form of the need to strengthen transparency in the disclosure of financial policies of public companies in the Indonesian capital market.